Persuasive Features of Scientific Explanations: Explanatory Schemata of Physical and Psychosocial Phenomena - Schoenherr, Jordan Richard; Thomson, Robert (Frontiers in Psychology, 2021)
Explanations are central to understanding the causal relationships between entities within the environment. Instead of examining basic heuristics and schemata that inform the acceptance or rejection of scientific explanations, recent studies have predominantly examined complex explanatory models. In the present study, we examined which essential features of explanatory schemata can account for phenomena that are attributed to domain-specific knowledge. In two experiments, participants judged the validity of logical syllogisms and reported confidence in their response. In addition to validity of the explanations, we manipulated whether scientists or people explained an animate or inanimate phenomenon using mechanistic (e.g., force, cause) or intentional explanatory terms (e.g., believes, wants). Results indicate that intentional explanations are generally considered to be less valid than mechanistic explanations and that ‘scientists’ are relatively more reliable sources of information of inanimate phenomena whereas 'people' are relatively more reliable sources of information of animate phenomena. Moreover, after controlling for participants’ performance, we found that they expressed greater overconfidence for valid intentional and invalid mechanistic explanation suggesting that the effect of belief-bias is greater in these conditions.